Design, Synthesis, and in Vitro Evaluation of 4‐(4‐Hydroxyphenyl)piperazine‐Based Compounds Targeting Tyrosinase. (26th September 2022) - Mirabile, Salvatore; Germanò, Maria Paola; Fais, Antonella; Lombardo, Lisa; Ricci, Federico; Floris, Sonia; Cacciola, Anna; Rapisarda, Antonio; Gitto, Rosaria; De Luca, Laura
Abstract: Melanin biosynthesis is enzymatically regulated by tyrosinase (TYR, EC 1.14.18.1), which is efficiently inhibited by natural and synthetic phenols, demonstrating potential therapeutic application for the treatment of several human diseases. Herein we report the inhibitory effects of a series of (4‐(4‐hydroxyphenyl)piperazin‐1‐yl)arylmethanone derivatives, that were designed, synthesised and assayed against TYR from Agaricus bisporus (AbTYR). The best inhibitory activity was predominantly found for compounds bearing selected hydrophobic ortho ‐substituents on the aroyl moiety (IC50 values in the range of 1.5–4.6 μM). They proved to be more potent than the reference compound kojic acid (IC50 =17.8 μM) and displayed competitive mechanism of inhibition of diphenolase activity of AbTYR. Docking simulation predicted their binding mode into the catalytic cavities of AbTYR and the modelled human TYR. In addition, these compounds displayed antioxidant activity combined with no cytotoxicity in MTT tests. Notably, the best inhibitor affected tyrosinase activity in α‐MSH‐stimulated B16F10 cells, thus demonstrating anti‐melanogenic activity. Abstract : Anti‐melanogenic agents: The design, synthesis, docking and inhibitory assays toward tyrosinase (TYR) from Agaricus bisporus (AbTYR) were performed for a series of (4‐(4‐hydroxyphenyl)piperazin‐1‐yl)arylmethanone derivatives. The most promising compound 10 displayed antioxidant activity combined with no cytotoxicity in MTT tests and exerted anti‐melanogenic effects on B16F10 cells.